ANALISIS INKLUSI KEUANGAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Ibrohim, Muhammad Andhika; Susilowati, Dwi; Yuli, Sri Budi Cantika (Journal of Financial Economics & Investment, 2025)
Economic growth and financial inclusion have a mutually reinforcing relationship. Financial inclusion consists of three indices, namely Availability, Access, and Usage. The purpose of this study is to determine the influence of the level of financial inclusion on economic growth in Indonesia and to determine which indicators most influence economic growth in Indonesia. The method used in this study is Partial Lie Square (PLS) analysis. The study period is 2017-2023 with quarterly data with independent variables (Financial Inclusion) as latent variables that have many indicators. The results of the analysis show that of the three latent variables of financial inclusion, there are two variables that affect economic growth, namely Access with indicators of debit cards, credit cards, and e-money cards. and Usage with indicators of debit transaction volume. The implication of the research results is that government and central bank policies are to encourage access and use of digital financial services in the community, especially those underserved by formal financial institutions as an effort to accelerate economic growth in Indonesia.